Molecular Identification Based on β-Tubulin of Trichomonas vaginalis Infection among Women in Babylon Province - Zainab Waddah Kermasha; Hayam Khalis Al-Masoudi; Suhaila Fadhil Mohammed (Medical Journal of Babylon)
Background: Trichomonas vaginalis (T. vaginalis) is an anaerobic flagellated parasite that usually infects the female genitourinary system. The traditional diagnostic tools of T. vaginalis, like wet-mount microscopy, have several limitations regarding technical requirements and accuracy. Consequently, to control the spread of trichomoniasis, fast and accurate detection of trichomoniasis represents a crucial factor in the treatment plan. Objectives: This study was performed to utilize polymerase chain reaction (PCR) assays as a diagnostic tool for T. vaginalis. Materials and Methods: Vaginal swabs were obtained from 186 women who were admitted to the gynecology clinic in Al Sadiq Hospital in Babil Governorate in Iraq. Additionally, a questionnaire was gathered from the female participants regarding their age, residency, history of abortion, and symptoms. DNAs were extracted from the swabs, and conserved β-tubulin genes were amplified using specific primers. Results: Of the 186 participant females, 40 women showed positive PCR outcomes of T. vaginalis β-tubulin gene versus only seven positive cases detected by wet-mount microscopy. Residency and age-related prevalence of T. vaginalis infection were not statistically significant, despite the higher positive cases reported in urban areas. Additionally, higher percentages of history of abortion were seen in infected females versus noninfected females. Clinical diagnosis demonstrated that vaginal discharge and itching were the most prevalent symptoms reported by infected females. Conclusion: PCR assay used in the current study showed a beneficial and fast diagnostic ability of T. vaginalis because of its high sensitivity and specificity. Consequently, this would blunt the transmission of trichomoniasis among individuals, especially infected patients with asymptomatic properties.